Paradigma Kebahagiaan Cinta Thomas Aquinas dan Pendidikan Seksualitas Kaum Religius dalam Summa Contra Gentiles (Pusat Riset dan Inovasi Nasional, 2026)
Human happiness does not lie in physical pleasure, victory, wealth, honour, worldly power, a beautiful body, or the senses. People in religious communities seek something deeper, contemplating and acknowledging the highest value in union with God. Thomas Aquinas, in his Summa Contra Gentiles, arguments that human happiness lies in the contemplation of God, through which one attains peace and fulfilment in total self-surrender to God. However, in the lived experience of religious communities, a fear of matters related to sexuality is evident. Indeed, some misunderstand and misinterpret these matters, resulting in monks and nuns who become cold, dry, and rigid, acting in ways that violate sexual morality, thereby disrupting or even destroying—their ministry due to such improper conduct. Based on this, the author recognises the importance of education and the appreciation of sexual values for religious communities. Using a literature review method involving relevant books, journals, articles, and Church documents with a theological approach, it was found that the education of religious people requires aspects of happiness and sexuality education. The results of the study indicate that Thomas Aquinas’s concept of happiness can bridge religious life with sexuality education, which is one aspect that must be understood and lived out. Therefore, the happiness of love and the sexuality education of religious people need to be explored and lived out in the course of living and experiencing life as a religious person.